Resistance training programs on bone related variables and functional independence of postmenopausal women in pharmacological treatment: A randomized controlled trial - Borba-Pinheiro, Claudio Joaquim (2016)
Introduction: Osteoporosis is a chronic disease that leads to bone fragility and is associated with fracture risks and serious consequences for mobility. Objective: To verify the effects of two linear programs of resistance training (RT) on bone mineral density (BMD), functional autonomy (FA), muscular strength and quality of life (QoL) of postmenopausal women in pharmacological treatment. Study design: Randomized controlled trial, code: RBR-6bqsw8. Methods: 52 volunteers were distributed into three groups, according to randomly parallel form: RT3times-per-week (RT3, n = 20); RT2times-per-week (RT2, n = 16) and control group (CG, n = 16). The following assessment tools were used: bone mineral density (BMD) by dual X-ray absorptiometry, 'Latin America Group for maturity' (GDLAM) protocol for FA, 10RM test for leg exercises and the 'Osteoporosis Assessment Questionnaire' (OPAQ) for QoL. The physical activities were planned for 13 months in cycles with different intensities. A two-way ANOVA with Bonferroni post-hoc test were used. Results: The results showed that the RT3/week was significantly more efficient (p < 0.05) compared with RT2/week, including: All BMD variables, FA (δ% = 29.3%), leg press at 45° (δ% = 24.97%) and OPAQ (δ% = 20.23%). In addition, both RT3 and RT2 groups were more efficient (p < 0.05) compared with CG, including: total BMD (δ% = 0.09%) and (δ% = 0.06%); FA (δ% = 7.1%) and RT2 (δ% = 3.78%); Leg press at 45° (δ% = 84.1%) and (δ% = 59.1%); keen extension (δ% = 15.28%) and (δ% = 20.37%); OPAQ (δ% = 57.61%) and (δ% = 37.37%), respectively. Conclusion: The study showed that both experimental groups presented favorable results for BMD, strength, FA and QoL. However, the RT3 showed the best results compared to other groups after 13 months of intervention.